LITHOSPHERIC STRUCTURE OF THE WESTERN PART OF THE EAST EUROPEAN CRATON INVESTIGATED BY DEEP SEISMIC PROFILES - Grad M.; Janik T.; Guterch A.; Środa P.; Czuba W.; Astapenko V.N.; Belinsky A.A.; Garetsky R.G.; Karatayev G.I.; Terletsky V.V.; Zlotski G.; Jensen S.L.; et al. (My University, 2006)
The Palaeoproterozoic collision of Archaean Fennoscandia, Volgo-Uralia and Sarmatia, viewed as a large composite of terranes, each with an independent history during Archaean and Early Proterozoic time, formed the East European Craton. This paper summarizes the results of deep seismic sounding investigations of the lithospheric structure of the southwestern part of the East European Craton. On the basis of the modern EUROBRIDGE'94-97, POLONAISE'97 and CELEBRATION 2000 projects, as well as of data from the Coast Profile and from reinterpreted profiles VIII and XXIV, the main tectonic units of Fennoscandia and Sarmatia are characterized. The crustal thickness in the whole area investigated is relatively uniform, being between 40 and 50 km (maximum about 55 km). For Fennoscandia, the crystalline crust of the craton can be generally divided into three parts, while in Sarmatia the transition between the middle and lower crust is smooth. For both areas, relatively high P-wave velocities (≥7.0 km/s) were observed in the lower crust. Relatively high seismic velocities of the sub-Moho mantle (~8.2-8.3 km/s) were observed along most of the profiles. The uppermost mantle reflectors often occur ca. 10 to 15 km below the Moho. Finally, we show the variability in physical properties for the major geological domains of Fennoscandia and Sarmatia, which were crossed by the network of our profiles.
Keywords: CRUSTAL STRUCTURE; DEEP SEISMIC REFRACTION; EAST EUROPEAN CRATON; MANTLE REFLECTORS; SEISMIC RAY-TRACING; Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой